Design and development of a sensor assembly based on 1-D photodiode arrays for distance offset measurements. (August 2022) - Patel, Sahejad; Alnumay, Yazeed; Brahim, Ahmed Al; Felemban, Amjad; Alrasheed, Ali J.; Jifri, Hesham; Parrott, Brian; Abdellatif, Fadl
Abstract: This paper proposes a sensing device to accurately measure lateral offsets for applications in calibration and alignment activities. The proposed sensor assembly is primarily designed and developed for use in volumetric calibration procedures of custody tanks in the energy industry. In order to achieve sub-millimeter accuracy levels for offset measurements, the sensor device utilizes multiple 1-D photodiode arrays in a specific configuration that enables improvement upon currently utilized procedures and devices. The presented design is also modular such that it can be easily modified to address applications involving robotic vehicles, and other systems that require tracking, measurement, alignment and calibration activities. The experimental evaluation of the proposed sensor assembly showed that it can measure distance offset measurements with a resolution of 125 μ m and a measured accuracy within 730 μ m . The promising results show that the proposed sensing device can be integrated into existing procedures that require high accuracy measurements. Highlights: A sequence of multiple light-sensing photodiodes used to measure distance offsets. Records accurate sub-millimeter readings that were validated experimentally. Various filter and case designs were proposed and tested. Initially designed for use in volumetric calibration of custody tanks. Applicable to similar metrology-based activities such as structural deformation.